Incidence of cutaneous malignant melanoma by socioeconomic status in Canada: 1992–2006. Issue 1 (December 2015) - Johnson-Obaseki, Stephanie; Labajian, Varant; Corsten, Martin; McDonald, James
Abstract Background There are no nationwide studies documenting changes in cutaneous malignant melanoma incidence or association of incidence with socioeconomic status (SES) in Canada. We sought to determine whether melanoma incidence increased from 1992 to 2006 and if there was an association between SES and melanoma incidence. Additionally, we studied whether there was a correlation between province of residence and melanoma incidence. Methods Cases from the Canadian Cancer Registry were reviewed. Demographic and socioeconomic information were extracted from the Canadian Census of Population data. Cases were linked to income quintiles by postal code. A negative binomial regression was performed to identify relationships among these variables. Results Overall incidence of melanoma in Canada increased by 67 % from 1992 to 2006 (p < 0.0001). The increase in incidence was greater for melanoma in situ compared with invasive melanoma (136 % versus 52 % [p < 0.0001]). Incidence was positively correlated with higher income quintiles; the incidence rates among patients in the lowest income quintiles were 67 % of that for the highest income quintiles (p < 0.0001). Discussion A wide variety of explanations have been postulated for an increased incidence in melanoma among persons of higher SES, including access to and awareness of screening, more access to vacations in sunny climates, and increased leisure time. Variations in incidence of melanoma by urban vs. rural location and province may indicate differences in access to dermatologists across Canada. Conclusions Melanoma incidence is increasing in Canada and is higher among people in high SES groups. This rise is likely due to a combination of factors including a true rise in incidence due to increases in sun exposure, and also an increased detection rate, particularly in those who are more aware of the disease and have access to resources for detection.